A facile green synthesis of tungsten nanoparticles through Micro-EDM. (2019) - Mondal, Surajit; Singh, P.K.; Bishwakarma, H.; Shubham; S.K.Mishra; Gupta, H.S.; A.K.Mishra; Das, A.K.
Abstract: Recently, generation of tungsten nanoparticles has been a dynamic research area in light of their outstanding physical and optical properties. These properties rely on the size, shape and composition of particles.In this context, Micro-EDM process was introduced through which tungsten nanoparticle has been generated.The morphological and particle size were obtained with variation of the pulse-on time and rotation speed of tool in micro-EDM process. The decrease in pulse on time and increase in tool rotation speed tends to promote the formation of smaller size nanoparticles.